Failed tracheal intubation during obstetric general anaesthesia: a literature review. Issue 4 (November 2015) - Kinsella, S.M.; Winton, A.L.; Mushambi, M.C.; Ramaswamy, K.; Swales, H.; Quinn, A.C.; Popat, M.
Highlights We reviewed four decades of literature on obstetric failed tracheal intubation. At caesarean, the failure to intubate rate is 1 per 443, 1 death per 44 100 general anaesthetics. The proportion of cases where general anaesthesia was continued has increased. The laryngeal mask is the preferred supraglottic device for continuing anaesthesia. Failed intubation contributes but is not the sole reason for poor neonatal outcome.